Stop and Fricative Devoicing in European Portuguese, Italian and German. (June 2015) - Pape, Daniel; Jesus, Luis MT
This paper describes a cross-linguistic production study of devoicing for European Portuguese (EP), Italian, and German. We recorded all stops and fricatives in four vowel contexts and two word positions. We computed the devoicing of the time-varying patterns throughout the stop and fricative duration. Our results show that regarding devoicing behaviour, EP is more similar to German than Italian. While Italian shows almost no devoicing of all phonologically voiced consonants, both EP and German show strong and consistent devoicing through the entire consonant. Differences in consonant position showed no effect for EP and Italian, but were significantly different for German. The height of the vowel context had an effect for German and EP. For EP, we showed that a more posterior place of articulation and low vowel context lead to significantly more devoicing. However, in contrast to German, we could not find an influence of consonant position on devoicing. The high devoicing for all phonologically voiced stops and fricatives and the vowel context influence are a surprising new result. With respect to voicing maintenance, EP is more like German than other Romance languages.